Needs Analysis of Physics E-Modules Based on Dual Space Inquiry Framework to Stimulate Students' Creative Thinking Ability on Static Fluid Material - Hayati, Fitri; Novitra, Fuja; Mufit, Fatni; Suherman, Dea Stivani (Physics Learning and Education, 2025)
In order to encourage students' creative thinking regarding static fluid material, this study aims to assess the need for physics e-modules based on the Dual Space Inquiry framework. This research employs a development (R&D) methodology using the Dick and Carey instructional design model. Descriptive quantitative data analysis was used in the study. The results showed that students’ creative thinking abilities were still categorized as low, with an average percentage of 24.22%. Observations revealed that the learning approach used had not effectively encouraged students’ creative thinking, and that teachers were still relying on print-based instructional resources. Furthermore, based on a questionnaire completed by students, static fluid was identified as a topic that is difficult for them to understand. In light of these issues, there is a need for teaching materials that are both technology-based and capable of stimulating students' creative thinking skills. Therefore, the researchers propose a physics e-module based on the Dual Space Inquiry framework as a solution to enhance students’ creative thinking in learning static fluid material.